2005
DOI: 10.1128/aem.71.9.5404-5410.2005
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular DNA in Single- and Multiple-Species Unsaturated Biofilms

Abstract: Microb. Ecol. 43:416-423, 2002).Here, we investigated the compositional similarity of eDNA to cellular DNA, the relative quantity of eDNA, and the terminal restriction fragment length polymorphism (TRFLP) community profile of eDNA in multiplespecies biofilms. By randomly amplified polymorphic DNA analysis, cellular DNA and eDNA appear identical for P. aeruginosa biofilms. Significantly more eDNA was produced in P. aeruginosa and Pseudomonas putida biofilms than in Rhodococcus erythropolis or Variovorax paradox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
192
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 264 publications
(202 citation statements)
references
References 64 publications
(58 reference statements)
7
192
0
2
Order By: Relevance
“…44). Several studies have shown that eDNA is an abundant component of the extracellular matrix of P. aeruginosa biofilm (34,35,45). DNase treatment has been shown to disrupt P. aeruginosa biofilm grown in vitro (35,46) and is used in combination with antibiotics to treat P. aeruginosa infections of cystic fibrosis patients (47).…”
Section: Discussionmentioning
confidence: 99%
“…44). Several studies have shown that eDNA is an abundant component of the extracellular matrix of P. aeruginosa biofilm (34,35,45). DNase treatment has been shown to disrupt P. aeruginosa biofilm grown in vitro (35,46) and is used in combination with antibiotics to treat P. aeruginosa infections of cystic fibrosis patients (47).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the significance of eDNA for cellular attachment and structural integrity has more recently been recognized for an increasing number of Gram-negative and Grampositive species (Whitchurch et al, 2002;Steinberger and Holden, 2005;Allesen-Holm et al, 2006;Moscoso et al, 2006;Jurcisek and Bakaletz, 2007;Qin et al, 2007;Izano et al, 2008;Thomas et al, 2008;Heijstra et al, 2009;Vilain et al, 2009;Harmsen et al, 2010;Lappann et al, 2010). Release of DNA in bacterial biofilms has mainly been attributed to the lysis of a cellular subpopulation, mediated by the activity of autolysis systems (Allesen-Holm et al, 2006;Rice et al, 2007;Thomas et al, 2008Thomas et al, , 2009Mann et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…Whitchurch et al (166) first demonstrated that P. aeruginosa PAO1 biofilm formation was significantly reduced under flowing conditions in the presence of DNase. eDNA has been subsequently shown to contribute to biofilm formation by clinical P. aeruginosa isolates as well as by a variety of bacterial species, including Staphylococcus epidermidis, through analyses of biofilm formation by lysis-defective mutants and of DNA removal from the biofilm matrix (67,117,133,146,150). The contribution of eDNA to attachment and biofilm formation, however, appears to be temporal: experiments utilizing DNase I have suggested that cells in young PAO1 biofilms are held together by eDNA, whereas the cells in more-mature PAO1 biofilms are held together primarily by components other than eDNA (98,166).…”
Section: Being Sticky Is the Keymentioning
confidence: 99%